Interdependent and independent roles of type I interferons and IL-6 in innate immune, neuroinflammatory and sickness behaviour responses to systemic poly I: C - CUNNINGHAM, COLM; HARKIN, ANDREW (My University, 2015)
Type I interferons (IFN-I) are expressed in the brain during many inflammatory and neurodegenerative conditions and have multiple effects on CNS function. IFN-I is readily induced in the brain by systemic administration of the viral mimetic, poly I:C (synthetic double-stranded RNA). We hypothesised that IFN-I contributes to systemically administered poly I:C-induced sickness behaviour, metabolic and neuroinflammatory changes. IFN-I receptor 1 deficient mice (IFNAR1-/-) displayed significantly attenuated poly I:C-induced hypothermia, hypoactivity and weight loss compared to WT C57BL/6 mice. This amelioration of sickness was associated with equivalent IL-1β and TNF-α responses but much reduced IL-6 responses in plasma, hypothalamus and hippocampus of IFNAR1-/- mice. IFN-β injection induced trivial IL-6 production and limited behavioural change and the poly I:C-induced IFN-β response did not preceed, and would not appear to mediate, IL-6 induction. Rather, IFNAR1-/- mice lack basal IFN-I activity, have lower STAT1 levels and show significantly lower levels of several inflammatory transcripts, including stat1. Basal IFN-I activity appears to play a facilitatory role in the full expression of the IL-6 response and activation of the tryptophan-kynurenine metabolism pathway. The deficient IL-6 response in IFNAR1-/- mice partially explains the observed incomplete sickness behaviour response. Reconstitution of circulating IL-6 revealed that the role of IFNAR in burrowing activity is mediated via IL-6, while IFN-I and IL-6 have additive effects on hypoactivity, but the role of IFN-I in anorexia is independent of IL-6. Hence, we have demonstrated both interdependent and independent roles for IFN-I and IL-6 in systemic inflammation-induced changes in brain function
PUBLISHED
Keywords: I interferons (IFN-I); I interferons (IFN-I)